Preliminary validation of mirrored scales for monitoring professional soccer training sessions - Morandi, R. F.; Pimenta, E. M.; Andrade, A. G. P.; Serpa, T. K. F.; Penna, E. M.; Costa, M. C. O.; Júnior, N. S. O.; Garcia, E. S. (Journal of Human Kinetics, 2020)
We aimed to create a single subjective method to assess both internal training loads and subsequent fatigue. This new training-fatigue (dose-response) scale (TFS) was composed of two similar scales with the same properties, metrics and construction criteria. These two scales were designed to rate the perceived exertion (RPETFS) and perceived fatigue (RPFTFS) in professional soccer players. Twenty-two athletes participated to establish reliability, and 15 participated to establish validity. For reliability, the intraclass correlation coefficient (ICC) and standard error of measurement (SEM) were used. For criterion validity, the Spearman`s correlation coefficient and linear regression analyses were applied. Associations between RPETFS and RPFTFS were verified by a chi square test, and a further factorial exploratory analysis was conducted. RPETFS and RPFTFS were found to be reliable (ICC 0.74 and 0.77, SEM 0.30 and 0.30, respectively) and valid. RPETFS was best explained by the internal load of the Banister training impulse (p < 0.001), while RPFTFS was best explained by the internal load of the Stagno training impulse (p < 0.001). An association was found between the scales (RPETFS and RPFTFS) in which training duration had a more substantial impact on these subjective perceptions than did training intensity (p < 0.01). RPETFS and RPFTFS scales are reliable and valid for monitoring training sessions in Brazilian professional soccer players. The simultaneous oscillations of the RPETFS and RPFTFS scores can be used by staff members to better plan weekly training programs based on doseresponse ratings. Finally, training duration must be carefully controlled because it has a greater impact than intensity on subjective perceptions.